The Influence Of Service Quality, Product Innovation And Promotion On Customer Loyalty On Donat Kampar Galesong District Of Takalar - Jumriani Ansar; Buyung Romadhoni; Syarthini Indrayani (International Journal of Economic Research and Financial Accounting, 2024)
The study aims to test the impact of service quality, product innovation and promotion on customer loyalty in Donat Kampar Galesong district of Takalar. The type of research used is the quantitative method. The sample used consisted of 94 samples selected using purposive sampling. Data in the sample uses primary data obtained using a distributed questionnaire. The data analysis methods used are validity tests, rehabilitation tests, classical assumption tests, double linear regression tests and hypothesis tests using SPSS version 25 analysis tools. The results of the research showed that the quality of service has a positive and significant impact on customer loyalty, product innovation has no and significant effect on client loyalty and promotion has a significant and positive impact on customers loyalty On Donat Kampar Galesong Takalar district.